Different Frequency Bands in Various Regions of the Brain Play Different Roles in the Onset and Wake-Sleep Stages of Infantile Spasms - Dong, Yan; Xu, Ruijuan; Zhang, Yaodong; Shi, Yali; Du, Kaixian; Jia, Tianming; Wang, Jun; Wang, Fang (Frontiers in Pediatrics, 2022)
Objective: The study aimed to identify the signatures of brain networks using electroencephalogram (EEG) in patients with infantile spasms (IS). Methods Scalp EEGs of subjects with IS were prospectively collected in the first year of life (n = 8; age range 4–8 months; 3 males, 5 females). Ten minutes of ictal and interictal EEGs were clipped and filtered into different EEG frequency bands. The values of each pair of EEG channels were directly compared between ictal with interictal onsets and the sleep-wake phase to calculate IS brain network attributes: characteristic path length (CPL), node degree (ND), clustering coefficient (CC), and betweenness centrality (BC). Results CPL, ND, and CC of the fast waves decreased while BC increased. CPL and BC of the slow waves decreased, while ND and CC increased during the IS ictal onset (P < 0.05). CPL of the alpha decreased, and BC increased during the waking time (P < 0.05). Conclusion The transmission capability of the fast waves, the local connectivity, and the defense capability of the slow waves during the IS ictal onset were enhanced. The alpha band played the most important role in both the global and local networks during the waking time. These may represent the brain network signatures of IS.